Deep learning-based mapping of land subsidence susceptibility using InSAR and geospatial data - Nguyen Thanh, Tuan; Phan Trong, Trinh; Vu Dang, Khac; Duc Nguyen, Dam; Tran Van, Phong; Nguyen Duc, Anh; Dao Ngoc, Dung; Prakash, Indra; Thai Pham, Binh (Vietnam Journal of Earth Sciences, 2026)
Land subsidence is one of the geotechnical phenomena that significantly affects infrastructure, construction, and sustainable urban development. Therefore, predicting and identifying areas susceptible to land subsidence has received increasing attention in recent studies. This study examines the application of deep learning models to spatial data analysis for predicting land subsidence susceptibility in the Hanoi area. Land subsidence data were obtained from satellite imagery and processed using a multi-temporal InSAR approach to determine surface deformation. They were then split into two datasets: 70% for training and 30% for validation. A total of 19 conditioning factors were used as input variables for the models, including aspect, slope, curvature, elevation, normalized difference vegetation index (NDVI), groundwater, engineering geology, hydrogeology, Holocene sediment thickness, land use/land cover (LULC), rainfall, topographic wetness index (TWI), and Landsat 8 spectral Bands 1–7. Four deep learning models, including CNN, LSTM, DRDN, and CNN-LSTM, were developed and compared to evaluate their predictive capability. The performance of the models was assessed using AUC, RMSE, MAE, and other evaluation metrics. The results show that all four models achieved good predictive performance, among which the DRDN model provided the best overall results, with AUC = 0.984, MAE = 0.064, and RMSE = 0.254 for the training dataset, while the corresponding values for the validation dataset were AUC = 0.957, MAE = 0.093, and RMSE = 0.305, indicating that the model has high accuracy and strong generalization capability in mapping land subsidence susceptibility in the study area. In addition, SHAP analysis revealed that Holocene sediment thickness and groundwater were the most important factors controlling land subsidence susceptibility in Hanoi.